COLLABORATIVE GOVERNANCE IN REALIZING SUSTAINABLE DEVELOPMENT GOALS (SDGS) IN CIBIRU WETAN VILLAGE CILEUNYI DISTRICT BANDUNG REGENCY - Saputri, Riska; Rohayatin, Titin; Fauzi, Lukman Munawar (GoAcademica CRP, 2025)
The title of this thesis is